2016
DOI: 10.1177/0884533616661012
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Gastrostomy Tube Removal in Patients With Dysphagia After Stroke

Abstract: Gastrostomy feeding tubes are commonly placed in patients with dysphagia after stroke. The subsequent removal of the tube is a primary goal during rehabilitation. The purpose of our review was to identify predictors and factors associated with gastrostomy tube removal in patients with dysphagia after stroke. We conducted a literature review following the PRISMA statement and included the search databases PubMed, Scopus, Web of Science, and CINAHL. Articles were included in the final analysis per predefined inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 32 publications
3
18
0
Order By: Relevance
“…Removal of G tubes was associated with a variety of factors, as found in a review of literature by Wilmskoetter, with the strongest predictor being the absence of aspiration on modified barium swallow. This reflects the importance of ongoing monitoring for improvement in the safety of swallowing so that OI can resume as quickly as it is deemed safe and efficient.…”
Section: Nutrition Hydration and Medicationmentioning
confidence: 99%
“…Removal of G tubes was associated with a variety of factors, as found in a review of literature by Wilmskoetter, with the strongest predictor being the absence of aspiration on modified barium swallow. This reflects the importance of ongoing monitoring for improvement in the safety of swallowing so that OI can resume as quickly as it is deemed safe and efficient.…”
Section: Nutrition Hydration and Medicationmentioning
confidence: 99%
“…Enteral nutrition via PEG is indicated in patients with dysphagia [ 3 ]. After the complete resumption of oral intake, the PEG tube can be removed [ 4 ]. Although the gastrostomy site closes spontaneously in most cases after the removal of the PEG tube, persistent gastrocutaneous fistula can occasionally occur [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with an acquired brain injury and their caregivers face a long rehabilitation journey with uncertain potential for recovery. Swallowing rehabilitation may have potential effects on physical and cognitive functions; however, a systematic review of 6 retrospective studies evaluating gastrostomy tube removal after stroke reported “disagreement regarding the majority of predictor or factors across the studies.” Little research has been performed on the effectiveness and related factors of swallowing rehabilitation.…”
Section: Introductionmentioning
confidence: 99%